2000
DOI: 10.1074/jbc.m007058200
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric Forms of the Metastasis-related Mts1 (S100A4) Protein Stimulate Neuronal Differentiation in Cultures of Rat Hippocampal Neurons

Abstract: Neuronal differentiation and axonal growth are controlled by a variety of factors including neurotrophic factors, extracellular matrix components, and cell adhesion molecules. Here we describe a novel and very efficient neuritogenic factor, the metastasis-related Mts1 protein, belonging to the S100 protein family. The oligomeric but not the dimeric form of Mts1 strongly induces differentiation of cultured hippocampal neurons. A mutant with a single Y75F amino acid substitution, which stabilizes the dimeric for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
180
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 148 publications
(191 citation statements)
references
References 41 publications
9
180
1
1
Order By: Relevance
“…which L is the neurite length in lm, d is the vertical distance between two grid lines, and J is the number of intersections between grid lines and neuritis (Novitskaya et al, 2000).…”
Section: Neural Survival and Neurite Outgrowth Assays In Vitromentioning
confidence: 99%
“…which L is the neurite length in lm, d is the vertical distance between two grid lines, and J is the number of intersections between grid lines and neuritis (Novitskaya et al, 2000).…”
Section: Neural Survival and Neurite Outgrowth Assays In Vitromentioning
confidence: 99%
“…Treatment of 3D cultures of SVEC 4-10 cells with the S100A4 oligomeric protein stimulated the formation of protrusions (Figure 1b and e). The addition of the Y75F mutant of S100A4 that is capable of forming dimers only (Novitskaya et al, 2000) did not stimulate growth of the protrusions (Figure 1c and e). The observed capillary-like growth was also stimulated by tumor necrosis factor-a (TNF-a) and hepatocyte growth factor (HGF), indicating that this assay could be used for analysis of the stimulatory effect of different angiogenic molecules.…”
Section: Stimulation Of Capillary-like Growth Of Microvascular Endothmentioning
confidence: 99%
“…It was shown that extracellular activity of S100A4 is associated with the oligomeric conformation of the protein (Novitskaya et al, 2000;Ambartsumian et al, 2001). This conformation is detected both in vitro, in the conditioned media from the cells secreting S100A4, and in vivo, in the blood serum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are also associated with human diseases, including inflammation, brain disorders, cancer, diabetes, heart failure, and pathological conditions of the skin and hair follicle. The basic structural and functional unit of most S100 proteins was previously thought to be a noncovalently associated antiparallel dimer; however, there is increasing evidence that some members assemble into higher order oligomers, thereby conferring their biological function (3)(4)(5)(6)(7).…”
mentioning
confidence: 99%